Model of Agents-Based Branchless Banking Services Development in Urban and Rural Area - Rini Rachmawati; Nur Muhammad Farda; Bowo Setiyono (Indonesian Journal of Geography, 2020)
The banking sector has experienced a far leap related to Information Communication and Technology (ICT)-based services. Among them is e-banking that has been used by the community, especially in urban areas. Likewise, the use of ATMs can be used to provide banking services to the wider community, so that it can replace most of the functions of services in banks. However, in communities outside of urban areas such as rural communities there are still limitations in accessing e-banking and ATM services. Limited use of e-banking because this service must use internet media or smart phones to access. Meanwhile, the limited use of ATMs due to the availability of ATMs in rural areas is not as much as in urban areas, considering that rural areas are areas with low settlement densities. Today, banks in Indonesia have provided branchless banking by enabling agents. Branchless banking is found in urban, suburban and rural areas. In previous research, the existence of branchless banking in the form of agents and their utilization by customers has been identified. From previous studies, maps of agent and customer density and analysis related to the condition of regional accessibility have been produced. This research is a further study focusing on sub districts area with high agent density in both rural, suburban and urban areas. The purpose of this research is to analyze the development model of agent-based branchless banking services. Data was collected through primary data through observation, structured interviews and measurement of coordinates of the location of agents and banking services in the form of ATMs and Banks. The final result is expected to be used as a model for the development of branchless banking services in Indonesia.